Promotion Media Through System Design Using Technology - Khirdany, Elvin Nury (International Journal of Computer and Information System (IJCIS), 2024)
As information technology continues to advance, it drives a wave of innovations that transform various industries and business practices. This evolution has led to significant diversification in product offerings and pricing strategies, resulting in heightened competition among businesses. In this competitive environment, both producers and consumers must navigate a myriad of choices, making effective product promotion essential. Gosako, an emerging online motorcycle taxi service in Sampang District, has established a solid reputation among local residents due to its reliable service and competitive pricing. Despite its popularity, Gosako's promotional efforts are currently limited to WhatsApp, which presents challenges for customers seeking information about ongoing promotions and services. This limitation restricts the company's ability to reach a broader audience and fully capitalize on its market potential. To address these challenges, this research proposes the development of a dedicated website as a comprehensive promotional platform for Gosako. The website aims to enhance customer access to information about services, promotions, and pricing, thereby fostering increased engagement and awareness among potential users. Data for this study will be collected through a combination of observation, interviews with stakeholders, and analysis of existing documentation. The research aims to achieve two primary objectives: (a) to expand promotional outreach, thereby enhancing brand visibility and increasing sales turnover; and (b) to streamline the purchasing process for customers, facilitating smoother transactions when utilizing Gosako's services. By leveraging digital platforms, this initiative seeks not only to strengthen Gosako's market position but also to improve customer satisfaction and loyalty, ultimately contributing to the service's long-term success.